Urgensi Pendekatan Multi dan Inter-disiplin Ilmu dalam Penanggulangan Bencana - Adiyoso, Wignyo (Bappenas Working Papers, 2021)
The intensity and serious impact of disasters threaten human life, including in Indonesia. A series of natural disasters such as floods, landslides, earthquakes, and tsunamis in the past decade have claimed thousands of lives and damaged property and destroyed social and cultural structures. Current pandemic as non-natural disaster also shows that Covid-19 become among deadliest of disasters. With the unpredictable characteristics of disaster events (especially natural and pandemic), it is urgent to find a collaboration model for effective disaster management. As a concept, an approach and a method disaster management is not a monodisciplinary, but cross-disciplinary, whether it is multidisciplinary, interdisciplinary or transdisciplinary. Using a description and information analysis approach using secondary data through the literature review, this study discusses the link and contribution issues of disaster management. The results of the discussion show that apart from being multidisciplinary, disaster management is also interdisciplinary and transdisciplinary. In the disaster management cycle, there are important roles that differ between multidisciplinary, interdisciplinary, and transdisciplinary. This preliminary finding may be useful for researchers, policy makers, disaster managers and others to start cooperating in reducing disaster risk. A more comprehensive and in-depth study is needed to see the relationship between disaster management and related sciences for strengthening disaster management in the future.